DEVELOPMENT OF POLISH FOREIGN TRADE IN AGRI-FOOD PRODUCTS AFTER POLAND&APOS;SACCESSION TO THE EU - Maria Grzelak; Elżbieta Roszko-Wójtowicz (Acta Scientiarum Polonorum. Oeconomia, 2015)
Trends in foreign trade have a huge impact on the country's position in the international market. Poland's accession to the EU was a breakthrough for the Polish foreign trade. This paper analyses trends in the Polish foreign trade in agri-food products in the years 2004-2014, after joining the European Single Market (ESM) and adopting the rules of Common Agricultural Policy (CAP). Since 2004, export growth rate in Polish agri-food products has been faster than the import one and Poland turned from an agricultural net importer to a net exporter. In the paper the value and the balance of trade in agri-food products were analysed. Further, the geographical structure of Poland's foreign trade broken-down into different groups of countries was discussed. The analysis showed that agricultural and food sector improved a lot using the opportunities offered by the accession to the EU. Development of the Polish agricultural trade proves that international competitiveness of Polish agriculture in the years 2004-2014 improved.